Settings Kontribusi Online Learning Dalam Membantu Mahasiswa Memahami Akuntansi - Luciana Haryono; Arief Fadhilah; Daniel (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2017)
Online learning is becoming an alternatives mode of study for students in studying accounting . This research aims to investigate the effectiveness of online learning in accounting learning process. This research was carried out by adopting DeLone and McLean model (2003) using Structural Equation Modeling (SEM) processed by STATA version 14. Respondents are the first year students of management undergraduate program, who took the introduction course of accounting. The course was facilitated by WileyPLUS, and online learning resources, as a supplementary materials of introductory accounting textbook, published by John Wiley and Sons. These research found positive relationships between information quality, system quality, service quality and user satisfaction and between user satisfaction and benefits. This paper provides empirical evidence to support that online learning effectively help students to study accounting better. Online learning providers need to improve the quality of the system and provide up to date information. Lecturers should be improve their contribution to assist students in using online learning.